Behavior of High Strength Concrete Subjected to Elevated Temperature - Anunai, R.; Siempu, Dr. Rakesh (International journal of innovative technology and exploring engineering, 2019)
The High strength concrete defined as per IS 456 as the concrete having characteristic compressive strength more than 65 MPa. The concrete when subject to fire i.e. elevated temperatures loses its properties at a rapid rate. In the present investigation, ordinary vibrated concrete of M90 grade was developed as per the IS 10262. The hardened properties of concrete like compressive strength and split tensile strength were determined for concrete at ordinary temperature. The concrete specimens were subjected to elevated temperatures of 400oC, 600 oC, and 800 oC and then the specimens were brought to room temperature under different cooling regimes like air cooling and water quenching. The compressive residual strength of concrete was determined and a typical compared was made with the control specimen. The decrease in compressive strength of concrete at 800 oC was high compared to that at 400 oC.